Conference on civil engineering problems in the colonies a collection of papers presented at the Institution in June 1954. (Institution of Civil Engineers, 1954)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 14-18 June 1954.